The Antimicrobial Resistance Crisis: An Inadvertent, Unfortunate but Nevertheless Informative Experiment in Evolutionary Biology - Michael, Carolyn A.; Gillings, Michael R.; Blaskovich, Mark A. T.; Franks, Ashley E. (Frontiers in Ecology and Evolution, 2021)
The global rise of antimicrobial resistance (AMR) phenotypes is an exemplar for rapid evolutionary response. Resistance arises as a consequence of humanity’s widespread and largely indiscriminate use of antimicrobial compounds. However, some features of this crisis remain perplexing. The remarkably widespread and rapid rise of diverse, novel and effective resistance phenotypes is in stark contrast to the apparent paucity of antimicrobial producers in the global microbiota. From the viewpoint of evolutionary theory, it should be possible to use selection coefficients to examine these phenomena. In this work we introduce an elaboration on the selection coefficient s termed selective efficiency, considering the genetic, metabolic, ecological and evolutionary impacts that accompany selective phenotypes. We then demonstrate the utility of the selective efficiency concept using AMR and antimicrobial production phenotypes as ‘worked examples’ of the concept. In accomplishing this objective, we also put forward cogent hypotheses to explain currently puzzling aspects of the AMR crisis. Finally, we extend the selective efficiency concept into a consideration of the ongoing management of the AMR crisis.